Pro-immigration Norwegian Church élite: what explains the pro-immigration attitudes and are alleged welfare challenges acknowledged? - Haugen, Hans Morten (Journal of contemporary religion, 2024)
Unlike political and business élites, few studies address attitudes among members of the church élite. Faced with politicians who refer to Christian heritage and values to justify restriction on immigration, we want to understand the attitudes of church leaders. This article draws on data from the Norwegian Leadership Surveys, conducted in 2000 and 2015, to identify attitudes to immigration and to the Norwegian welfare system among the Norwegian Church élite. The church élite respondents were recruited among bishops, deans, and members of the National Church Council in the Lutheran majority church, the Church of Norway. Finding that a pro-immigration position characterizes the Church élite, we explore how these attitudes can be understood by introducing various variables. As immigration allegedly represents challenges to socio-economic integration and to upholding the welfare state, we investigate whether pro-immigration attitudes correlate with attitudes to promoting integration and upholding the welfare state. We find that pro-immigration attitudes are correlated with concern for those not able to provide for themselves, stronger trust in the State than in markets, and no particular concern for the impact on the welfare state. Opposing a nationalist protection discourse, the church leaders express a humanistic or human-centered protection discourse, which we term ‘human-centered cosmopolitanism’.